Prognostic significance of microRNA-200b and ERCC1 expression in tumor cells of patients with esophageal cancer - Kirkilevsky, S.I.; Krakhmalev, P.S.; Malyshok, N.V.; Zadvornyi, T.V.; Borikun, T.V.; Yalovenko, T.M. (PH Akademperiodyka, 2023)
Summary. Background: The development of malignant tumors, including esophageal cancer (EC), could be associated with impaired expression of oncosuppressive miRNA-200b and еxcision repair cross-complementing group-1 (ERCC1), a protein involved in DNA repair and alternative splicing. Aim: To investigate the features of expression of miRNA-200b and ERCC1 in tumor cells of patients with EC and to determine the possibility of their use for prediction of EC aggressiveness. Materials and Methods: 52 patients with EC of stages II–IV were enrolled. Expression of ERCC1 in tumor cells was assessed by immunohistochemical method, expression of miRNA-200b was evaluated by the real time reverse transcription-polymerase chain reaction. Results: The expression of miRNA-200b and ERCC1 in tumor cells of EC patients is associated with their life expectancy. The characteristic features of neoplasms in patients who died within 12 months are low expression of miRNA-200b (2.87 ± 1.65 a.u.) (ρ = –0.42; p < 0.05) and high expression of ERCC1 (191.0 ± 18.6 H-Score points) (ρ = –0.48; p < 0.05). The inverse correlations between the level of miRNA-200b expression and the tumor size were found both in the group of patients with survival < 12 months (ρ = –0.42; p < 0.05) and in the group of patients with survival > 12 months after surgery (ρ = –0.53; p < 0.05). Conclusions: The obtained data indicate the feasibility of using the expression of miRNA-200b and ERCC1 in EC cells to predict the aggressiveness of esophageal cancer.